Antecedents of Financial Inclusion: Evidence from Tripura, India - Singh, Ranjit; Roy, Sankharaj; Pandiya, Bhartrihari (Indian Journal of Finance and Banking, 2020)
The present research assesses the determinants of financial inclusion of members of Self Help Groups (SHGs). The research work is done with primary data collection from around 380 members who are beneficiaries of 95 SHGs in Tripura, India. After performing factor analysis, six major factors named Physical Infrastructure, Financial Awareness, IT Infrastructure, Suitability of Financial Products, Ease of Banking and Economic Status of members of SHGs were identified as major factors that play a pivotal role in bringing financial inclusion of the members of SHG. In these 6 factors, some other factors were also added such as age, income, education, landholding, the regularity of income, earning members count, gender, caste, location, religion, etc. Fitting ordinal logistic regression model, it was found that, the important factors that have an impact on financial inclusion on the members of the SHGs are financial awareness, ease of banking and economic status of the members, the relevance of financial products, physical infrastructure, monthly income, landholding, education, age and their status with respect to the BPL category. The decision-makers in power should collaborate with financial institutions should consider and apply this finding during the disbursement of loans.